PENGARUH GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN INSTANSI PEMERINTAH PADA KABUPATEN ACEH BESAR - Emmi Suryani; Ismail Ismail (STIE DWI SAKTI BATURAJA, 2018)
This research is empirical, where the purpose of this study is to determine the effect of the level of understanding of the principles of accountability, transparency and public participation both partially and simultaneously (together) on the quality of the financial statements of the Aceh Provincial Government.The population in this study were all of the Dinas in Aceh Province as many as 38 Agencies, which included the Secretariat, Offices, Regional Technical Agencies, and Bodies in the Aceh Besar District Government. While 115 people were taken as a sample, the sample of this study will be taken using a proportionate stratified random sampling technique. While the results of testing simultaneously obtained Fcount of 41,819, while Ftable at the significance level ï‚µ = 5% is equal to 2.686. This shows that Fcount> Ftable, with a probability level of 0.000. Thus the results of this calculation can be taken as a decision that accepts alternative hypotheses and rejects the null hypothesis, meaning that the variables of accountability (x1), transparency (x2) and public participation (x3), together have a significant effect on the quality of the financial statements of the Agency Aceh Besar Government.While partially the accountability variables (x1), transparency (x2), public participation (x3) also affect the quality of the financial statements of the Government of Aceh Besar.